Sirenomelia in an Iraqi twin: a case report - Hassan, Moaied A. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Sirenomelia is a rare congenital malformation characterized by fusion of the lower limbs giving a characteristic mermaid-like appearance to the affected fetus. It is commonly associated with gastrointestinal, genitourinary, cardiovascular and musculoskeletal system defects. Objective : To report the clinical manifestations of an extremely rare and complex malformation along with the associated anomalies. Case report: A case of sirenomelia was reported in a one of a set of twin delivered at term by caesarean section to a 39 year old Iraqi mother. According to the search that has been done, it seems that this is the first reported case in this country. The following associated anomalies ( imperforate anus, absence of external genitourinary orifices, esophageal atresia with tracheo-esophageal fistula, intestinal atresia and bilateral renal agenesis ) were observed. Conclusion: Sirenomelia is a rare and fatal congenital malformation. Still there is some controversy regarding its etiology, however there is an increasing belief that this complex malformation is distinct from the caudal regression syndrome. Survival depends on the presence of normal renal function